Nature as Culture of Penghayat: The Landscape, Reaction, and Movement of Penghayat in Cilacap - Siti Khoir Nafiya (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2019)
This article aims to explain how Penghayat does not remain silent when their views and their ritual practice are questioned. This paper explains about Penghayat views that nature as a looking way in their daily lives and practices. They use metaphors such as folksong or traditional art contained in nature to interaction and reaction, not only with their members/citizens (self) but also with other people (others). They have knowledge about nature presenting and functioning. The knowledge of the Jagad Gumelar ginulung in Jagad Alit is the blueprint, as guiding, from their Kaki and Nini (ancestors) spoken. With ethnographic research and landscape discourse, the author reveals how nature is seen as a culture in society. The rituals show how the values of the role of nature, both the universe and the human self contribute to daily life, including Penghayat belief.